Banana and plantain breeding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Banana and plantain breeding strategies / Persley. G.J. and E.A. De Langhe (eds.), 1987. ACIAR Proceedings No. 21, 187 pp.